Sensitization to Aeroallergens in Korean Children: A Populationbased Study in 2010 - 김지현; 함명일; 이소연; 김우경; 채유미; 박용민; 한만용; 이기재; 권호장; 정진아; 김수영; 안강모 (Journal of Korean medical science, 2011)
We performed this study to assess the prevalence of sensitization to aeroallergens and to analyze the difference between prevalence rates according to children’s ages and residential areas. In this nationwide cross-sectional study, first grade students of 45 elementary schools and 40 middle schools were randomly selected, and skin prick tests were performed for 18 inhalant allergens between October and November 2010. Of 7,829 analyzed subjects, 3,753 (47.9%) were sensitized to at least one aeroallergen. Sensitization to Dermatophagoides farinae was found to be the most prevalent in elementary schoolchildren (32.4%), followed by Dermatophagoides pteronyssinus, Tyrophagus putrescentiae, Japanese hop, and oak. In middle schoolchildren, D. pteronyssinus yielded the highest prevalence (42.7%), followed by D. farinae, T. putrescentiae, Japanese hop,and cat. In middle schoolchildren, the sensitization rate to aeroallergens in metropolitan,urban, and rural areas was 57.2%, 54.3%, and 49.8%, respectively (P = 0.019). In this age group, the sensitization rate in low, middle, high, and very high income groups was 53.8%, 51.8%, 59.0%, and 59.6%, respectively (P = 0.002). In conclusion, the sensitization rate is 47.9% and house dust mite is the most prevalent allergen in the pediatric population in Korea. The rate is higher in metropolitan areas and the highest income group than in rural areas and low income groups. KCI Citation Count: 12